Effect of Ideal Amino Acid Ratio of Arginine to Lysine on Intake, Nutrient Digestibility, Growth Performance, Antibody Titers of Newcastle Disease and Infectious Bronchitis Disease, and Carcass Characteristics of Broilers - Wahab Liaqat; Urooj Anwar; Asfa Fatima; Azhar Rafique; Riaz Mustafa; Umar Farooq; Faisal Ramzan; Waseem Abbas; Muhammad Farooq Khalid; Muhammad Ashraf; Muhammad Riaz; Muhammad Qamar Bilal; et al. (Animals)
This study aimed to assess the effects of different arginine (Arg) to lysine (Lys) ratios on feed intake, nutrient digestibility, growth performance, carcass characteristics, and antibody titers of Newcastle disease (ND) and infectious bronchitis (IB) disease in broilers during 35 days of trial. For this purpose, a total of 816 day-old broiler birds having an average weight of 38 ± 3 g were divided into six dietary treatments in such a way that each treatment had eight replicates and each replicate had 17 birds. The treatments were 0.95 (1.19/1.25, 1.12/1.18, and 1.05/1.1), 1 (1.25/1.25, 1.18/1.18, and 1.1/1.1), 1.05 (1.31/1.25, 1.24/1.18, and 1.17/1.1), 1.10 (1.38/1.25, 1.30/1.18, and 1.23/1.1), 1.15 (1.44/1.25, 1.36/1.18, and 1.28/1.1), and 1.20 (1.50/1.25, 1.42/1.18, and 1.34/1.1) Arg/Lys divided into different amounts according to the nutritional needs of starter, grower, and finisher diets, respectively. The results showed that in the finisher phase, the FI was influenced cubically, while in the overall period, a quadratic effect was observed for the FI (p < 0.05). The results of BWG showed that BWG was linearly increased in birds given different Arg/Lys in the grower, finisher, and overall period (p < 0.05). The results also showed that during the grower, finisher, and overall phases, the body weight gain (BWG) was better in birds fed with 1.05 and 1.10 Arg/Lys (p < 0.05). Furthermore, a better feed conversion ratio (FCR) was shown in the starter and grower phases at 1.10 and 1.15 Arg/Lys (p < 0.05). The results of nutrient digestibility explored showed that the experimental treatments had a better effect (p < 0.05) on dry matter and crude fat digestibility in birds fed with 1.19/1.25, 1.12/1.18, and 1.05/1.1 and 1.25/1.25, 1.18/1.18, and 1.1/1.1 Arg/Lys in their diets while the crude protein digestibility remained unaffected with different treatments (p > 0.05). The treatments had no effect (p > 0.05) on relative organ weights, immune organs, and carcass characteristics. However, higher titers of ND and IBD were observed in birds fed with Arg/Lys of 1.38/1.25, 1.30/1.18, and 1.23/1.1 and 1.50/1.25, 1.42/1.18, and 1.34/1.1 in their diets (p < 0.05). Based on the results of the current study, it is concluded that the inclusion levels of 1.38/1.25, 1.30/1.18, and 1.23/1.1, and 1.44/1.25, 1.36/1.18, and 1.28/1.1 Arg/Lys resulted in better growth performance and immune response in the broiler birds, respectively. Therefore, adjusting the levels of Arg/Lys in feed is recommended to enhance broilers’ growth performance and immune response.